Parameter Biokinetika dari Degradasi Limbah Kol dan Tomat Menggunakan Sistem Bioreaktor Anaerobik - Sarah, Maya; Misran, Erni; Maulina, Seri; Pertiwi, Ika; Ritman, Nahlionny; Hasibuan, Isti Madinah; Parulian, Ihut (Jurnal Teknik Kimia USU, 2021)
The world's energy supply is very dependent on non-renewable energy in the form of fossil fuels. This causes fossil fuels depletion and the need for alternative energy sources such as biogas. Biogas is produced from the fermentation process of organic matter with the help of anaerobic bacteria in free oxygen absence. This study aims to produce biogas from cabbage and tomato waste separately. Biogas production was carried out by varying feed concentrations of 100 g/L, 200 g/L, and 300 g/L for cabbage waste and 81.6 g/L; 215 g/L; and 237 g/L for tomato waste. This study consisted of 10 days seeding and acclimatization process, followed by a start-up stage using insulated anaerobic bioreactors. The largest methane from cabbage and tomato waste was 60% at a feed concentration of 200 g/L and 50% at a feed concentration of 237 g/L, respectively. The maximum growth rates (Âµm) for biogas from cabbage and tomato waste were 0.122 day-1 and 0.121 day-1, respectively.